Evaluasi Faktor Penyebab Keterlambatan Bongkar Muat Batubara dan Strategi Penanganannya pada PT. Bahtera Adhiguna Cabang Merak: Penelitian - Meriah Kita Deliani; Lia Safitri Br Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Coal loading and unloading operations play a vital role in ensuring the continuity of energy supply, particularly for electricity generation and industrial activities. PT Bahtera Adhiguna, as a shipping company engaged in coal transportation, frequently encounters delays during loading and unloading processes at ports, which disrupt operational schedules and increase operational costs. This study aims to evaluate the factors contributing to delays in coal handling operations and to formulate appropriate strategies to mitigate these issues at PT Bahtera Adhiguna Branch Merak. The research employed a qualitative descriptive approach through field research and literature review. Field data were obtained through direct observation of loading and unloading activities, while secondary data were collected from relevant regulations, company documents, and supporting literature. The results indicate that delays are primarily caused by adverse weather conditions, inadequate loading and unloading equipment, poor coordination among stakeholders, and technical problems experienced by vessels. Based on these findings, several handling strategies are proposed, including improving operational scheduling, enhancing port facilities and equipment readiness, strengthening coordination between ship operators and port authorities, and optimizing communication systems.